The War of Ideas : Jihadism Against Democracy - Phares, Walid (Palgrave Macmillan, 2007)
From Afghanistan and Iraq to Europe and the U.S., we are engaged in one of the most heated wars of all time. In this incisive book, terrorism expert Walid Phares shows that the most important battle of all is taking place in the hearts and minds of people across the world. This is the War of Ideas, where ideology is the most powerful weapon. Phares looks at the two opposing camps, one standing for democracy and human rights, the other rejecting the global community and calling for jihad against the West. He reveals the strategies of both sides, explaining how new technology and the jihadists' media savvy have raised the stakes in the conflict. And most urgently, he warns that we are in danger of losing the war, for while debate and theorizing rarely lead to action, ideas and deeds are inextricably linked for the forces of jiha